LINES PLAN OF PURSE SEINE SHIP IN SOUTH SULAWESI - Alham, Irawan; Lendri, Lendri (Journal of Agriculture, 2022)
Vessels used for purse seine fishing gear operations in South Sulawesi are made of teak wood (Tectona grandis), spinach with a length of 13 – 25 m, a width of 3.30 – 5.87 m and a height of 1 – 1.8 m. Based on the classification of durability and strength of wooden ships, types of teak and spinach are classified as durable class I and strong class II. Good wood for ship building is one that has a durable class I – II and a strong class I – II (Wibowo 1981 in Marlin, 2008). This means that vessels operating purse seine fishing gear in South Sulawesi are well used because they have relatively large durability and strength. Purse seine vessels in this area have a tonnage between 10 – 35 GT. GT calculation based on Director General of PERLA No, PY.67/1/16-02. The main engine used consists of two units of Yanmar brand, Mitsubishi and Yun chai with a power of 20, 27 or 30 PK. In addition, it is also equipped with a 15 PK Jian Dong brand roller machine